2001
DOI: 10.1556/aphysiol.88.2001.3-4.12
|View full text |Cite
|
Sign up to set email alerts
|

Histological and biochemical effects of cigarette smoke on lungs

Abstract: In this study, rats were made to inhale cigarette smoke in a specifically prepared container for different periods. The lung tissue samples of the subjects were examined by light microscopy, transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Malonaldehyde, one of the free oxygen radicals was determined in lungs and plasma. The catalase activity level of erythrocyte and arginase levels were determined. Three groups were formed. The rats in the Ist and IInd groups were made to inhale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
2
0
0
Order By: Relevance
“…PM administration decreased their levels slightly in heart and markedly in lung and brain tissues. Elevated MDA and PC levels in CS group were compatible with the results of previous studies (Altuntas et al, 2002;Baskaran et al, 1999;Luchese et al, 2007;Ozan et al, 2001;Panda et al, 2001; Valenca et al, 2008). These results demonstrated that PM can decrease the toxicity of CS-mediated free radicals and sustained normal cell integrity.…”
Section: Discussionsupporting
confidence: 90%
“…PM administration decreased their levels slightly in heart and markedly in lung and brain tissues. Elevated MDA and PC levels in CS group were compatible with the results of previous studies (Altuntas et al, 2002;Baskaran et al, 1999;Luchese et al, 2007;Ozan et al, 2001;Panda et al, 2001; Valenca et al, 2008). These results demonstrated that PM can decrease the toxicity of CS-mediated free radicals and sustained normal cell integrity.…”
Section: Discussionsupporting
confidence: 90%
“…In these studies, cigarette exposure was shown to be associated with elevated MDA levels in pulmonary as well as testicular tissues. 32,33 The results of the study conducted by Husain et al 34 and the findings of our study have parallelisms. Indeed, Husain et al similarly report that cigarette exposure causes an increase in hepatic MDA levels.…”
Section: Discussionsupporting
confidence: 86%